Growth and survival of Propagules of three mangrove species Rhizophora mucronata, Rhizophora apiculata and Avicannia Officinalis at different salinity levels. - Baylon, Pamela (UPHSI, 2000)
Mangroves are land plants that have developed certain features and adaptations in order to survive in the intertidal zone. Mangroves are important to people because these plants directly support local and offshore fisheries, provide physical protection from erosion and serve as habitat for wildlife. A study was made wherein the propagules of Rhizophora mucronata, Rhizophora apiculata, and Avicennia officinalis were planted to determine the growth and survival at different salinity levels. The salinity levels tested were 0 ppt, 10 ppt, 20 ppt, 30 ppt, and 40 ppt. The mangrove propagules were planted in black plastic bags, randomly distributed in a well-lighted area and watered daily, morning and afternoon. The growth of the propagules were measured every week with the use of Vernier caliper and culture lasted for 12 weeks. Results showed that Rhizophora mucronata grows best at 20 ppt which was significantly higher compared with the growth at other salinity levels based on one-way ANOVA. Growth of Rhizophora apiculata was highest at 0 ppt and Avicinnia officinalis was at 10 ppt. One-way analysis of variance, however, did not show significant difference on the growth of these two propagules at all salinity levels tested. Using the two-way ANOVA, Rhizophora mucronata showed significantly the highest growth compared with the other two species in all salinity levels tested.